Ù†ØµÙŠØØ© Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† ÙˆØªØ°ÙƒØ±Ø© Ø§Ù„Ù…Ø¤Ù…Ù†ÙŠÙ† Ù„Ù„Ø´ÙŠØ® Ø¹Ø¨Ø¯ Ø§Ù„ØµÙ…Ø¯ Ø§Ù„Ø¬Ø§ÙˆÙ‰ Ø§Ù„ÙÙ„Ù…Ø¨Ø§Ù†Ù‰ (1112Ù‡Ù€- 1203Ù‡Ù€) ØªØÙ‚ÙŠÙ‚Ù‡Ø§ ÙˆØªØ®Ø±ÙŠØ¬ Ø£ØØ§Ø¯ÙŠØ«Ù‡Ø§ Ø§Ù„Ù†Ø¨ÙˆÙŠØ© ÙÙŠÙ‡Ø§ - ÙŠÙ†ØªÙ‰, Ø³Ø§Ø±Ù‰ (Buletin Al-Turas, 2015)
Â Ø¥Ù† Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø¯ÙŠÙ† Ø³Ù„ÙŠÙ… ÙƒØ§Ù…Ù„ Ù…ÙˆØ§ÙÙ‚ Ù„Ø¹Ù‚ÙˆÙ„ Ø§Ù„Ø¥Ù†Ø³Ø§Ù†, ÙŠØºÙŠØ± ØØ¶Ø§Ø±Ø© Ø§Ù„Ø´Ø¹ÙˆØ¨ Ø¹Ù„Ù‰ Ø³Ù„ÙˆÙƒÙ‡Ø§ ÙˆØ£Ø®Ù„Ø§Ù‚Ù‡Ø§ ÙˆØ¹Ù‚ÙŠØ¯ØªÙ‡Ø§. ÙˆÙƒØ§Ù† Ø§Ù†ØªØ´Ø§Ø±Ù‡ Ù†Ø§Ø¬ØØ§ Ø¨ÙØ¶Ù„ Ø§Ù„Ø¹Ù„ÙˆÙ… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ù…Ù†Ù‡Ø§ Ø¹Ù„Ù… Ø§Ù„ØªØµÙˆÙ Ù„Ø£Ù†Ù‡ ÙŠÙ‚Ù Ù…ÙˆÙ‚Ù Ø§Ù„ØªØ³Ø§Ù…Ø Ù„Ù„ØØ¶Ø§Ø±Ø© Ø§Ù„Ù…ØÙ„ÙŠØ©, ÙˆÙ…Ù† Ø£Ù‡Ù… Ø¢Ø«Ø§Ø±Ù‡Ø§ Ù…Ø®Ø·ÙˆØ·Ø§Øª Ø«Ù…ÙŠÙ†Ø© Ø§Ù„Ù‚ÙŠÙ…. ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø© Ø§Ø®ØªØ±Øª Ø§ØØ¯Ù‰ Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø§Øª Ù„Ø¯Ø±Ø§Ø³ØªÙ‡Ø§, ØªØØª Ø¹Ù†ÙˆØ§Ù† " Ù†ØµÙŠØØ© Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† ÙˆØªØ°ÙƒØ±Ø© Ø§Ù„Ù…Ø¤Ù…Ù†ÙŠÙ†"ÙÙŠÙ‡Ø§ Ø¨ÙŠØ§Ù† Ø¹Ù† Ø§Ù„Ø¬Ù‡Ø§Ø¯ ÙÙŠ Ø³Ø¨ÙŠÙ„ Ø§Ù„Ù„Ù‡ Ùˆ ÙØ¶Ø§Ø¦Ù„Ù‡, ÙˆÙŠÙ†Ù‚Ø³Ù… Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ÙˆØµÙ Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø©, ÙˆØªÙ‚Ø¯ÙŠÙ… ØÙŠØ§Ø© Ù…Ø¤Ù„Ù Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø©, ÙˆØªØÙ‚ÙŠÙ‚ Ø§Ù„Ù†Øµ ÙˆØ§Ù„Ø£ÙÙƒØ§Ø± Ø§Ù„Ù‡Ø§Ù…Ø© Ø§Ù„ØªÙ‰ ÙˆØ±Ø¯Øª ÙÙŠ Ø§Ù„Ù†Øµ, Ùˆ ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù†Øµ Ø¥Ù„Ù‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© ÙˆØ£Ù…Ø§ Ø§Ù„ØºØ±Ø¶ Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙÙ‡Ùˆ:ØªÙ‚Ø¯ÙŠÙ… Ø§Ù„Ù†Øµ Ù„ÙŠØ³Ù‡Ù„Â  Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙÙŠ ÙÙ‡Ù…Ù‡ ÙˆØ¨ÙŠØ§Ù† Ù…Ù‚Ø§ØµØ¯Ù‡ ØØªÙ‰ ØªØ¹Ù… Ø§Ù„ÙØ§Ø¦Ø¯Ø© Ø¨Ø¹Ø¯ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø©.ÙˆØ§Ù„Ø¬Ø¯ÙŠØ± Ø¨Ø§Ù„Ø°ÙƒØ± Ù‡Ù†Ø§ ÙØ£Ù†Ø§ ÙƒØ§Ù„Ø¨Ø§ØØ«Ø© Ø£Ù‚ÙˆÙ… Ø¨ØªØ®Ø±ÙŠØ¬ Ø§Ù„Ø£ØØ§Ø¯ÙŠØ« ÙÙŠÙ‡Ø§ ÙˆÙ‡Ø°Ù‡ Ø§Ù„Ù†Ø³Ø®Ø© ØªØ´ØªÙ…Ù„ Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø®Ø·ÙˆØ·ØªÙŠÙ† ÙØÙ‚Ù‚ØªÙ‡Ù…Ø§ Ø¨Ø¹Ù…Ù„ Ø¯Ø±Ø§Ø³Ø© Ù…Ù‚Ø§Ø±Ù†Ø© Ù„Ø¥Ø®ØªÙŠØ§Ø± Ø§Ù„Ù†Ø³Ø®Ø© Ø§Ù„Ø¬ÙŠØ¯Ø© ÙˆØ§Ø¹ØªÙ…Ø¯Øª Ø¨Ù…Ù†Ù‡Ø¬ Ø³ØªØ§Ù†Ø¯Ø§Ø± Ø§Ù„Ø°ÙŠ ØµØÙŠØØ§ ÙˆÙ‡Ùˆ Ø§Ù„Ø¥Ø¹ØªÙ…Ø§Ø¯ Ø¹Ù„Ù‰ Ø§Ù„Ù†Ø³Ø®Ø© Ø§Ù„ØªÙ‰ ØªØ¹ÙŠØ¯ Ø£ÙƒØ«Ø±Ù‡Ø§ ØµØÙŠØØ§ ÙˆÙ…Ø¹ Ø§Ù„Ø¥Ø´Ø§Ø±Ø© Ø¥Ù„Ù‰ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„ÙˆØ§Ø±Ø¯Ø© ÙÙŠ Ø§Ù„Ù†Øµ Ø§Ù„ØªÙ‰ ÙˆØ¶Ø¹ØªÙ‡Ø§ ÙÙŠ Ø§Ù„Ù‡Ø§Ù…Ø´.Ù„Ù„Ù…Ø®Ø·ÙˆØ·Ø©Â  Ø£Ù‡Ù…ÙŠØ© Ø¨Ù„ÙŠØºØ© Ùˆ Ø«Ù…ÙŠÙ†Ø© ÙˆØ¢Ø«Ø§Ø± ÙƒØ¨ÙŠØ±Ø©, Ø®Ø§ØµØ© ÙÙŠ ØªÙ†Ù…ÙŠØ© ÙÙƒØ±Ø© Ø¹Ù† ØØ§Ù„Ø© Ø§Ù„Ø«Ù‚Ø§ÙØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙˆØªÙ‚Ø¯Ù…Ù‡Ø§, ÙƒÙ…Ø§ Ø£Ù†Ù‡Ø§ ØªØÙØ¸ Ø¹Ù„Ù‰ Ø§Ù„ØªØ±Ø§Ø« Ø§Ù„Ù‚Ø¯ÙŠÙ… ÙÙŠ Ø§Ù„Ø¹Ø§Ù„Ù… ÙˆØªØ¤Ø¯ÙŠ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø§Øª Ø¥Ù„Ù‰ ØªÙˆØ§ØµÙ„ Ø§Ù„Ø£Ø¬ÙŠØ§Ù„ ÙˆØªØ±Ø§Ø¨Ø· Ø§Ù„Ø£Ù…Ù… ÙˆØ§Ø²Ø¯Ù‡Ø§Ø± Ø§Ù„ØØ¶Ø§Ø±Ø§Øª, Ù„Ø£Ù† ÙÙŠÙ‡Ø§ Ù…Ø¹Ù„ÙˆÙ…Ø© ÙƒØ«ÙŠØ±Ø© ÙŠÙ„Ø²Ù… Ù„Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ù…Ø¹Ø±ÙØªÙ‡Ø§.---AbstractIslam is a religion full sound OK to human minds, alters the civilization of peoples on the behavior and morals and faith. It was successful thanks to the spread of Islamic Sciences them aware of mysticism because it stand the local tolerance of civilization, and the most important effects of precious manuscripts values.On this occasion, I chose one of the manuscripts for study, titled "Advice Muslims and ticket believers," the statement from the Jihad for the sake of God and the virtues, is divided Find a description of the manuscript, and make the life of the author of the manuscript, and the achievement of important text contained in the text, and translate text to and ideas Indonesian language and the purpose of this research is: to provide the text for easy reading in his understanding and statement purposes until the benefit after studying Almkhtooth.walagdir mentioning here I Kalpagesh I graduated conversations in this version include Almkhtoottin Vhakguethma doing a comparative study to choose the good version and adopted the approach Standard that right It is relying on the version that will restore the most correct and with reference to the errors contained in the text drawn up by the marginThe manuscript importance eloquent and precious and great effects, especially in the development of the idea on the status of Islamic culture and progress, as it kept the ancient heritage of the world and lead the study of manuscripts to the continuity of generations and the interdependence of nations and civilizations flourished, because the many information necessary for university students know